Lowering COVID-19 vaccine hesitancy among immigrants in Norway: Opinions and suggestions by immigrants - Kour, Prabhjot; Gele, Abdi; Aambø, Arild; Qureshi, Samera A.; Sheikh, Naima Said; Vedaa, Øystein; Indseth, Thor (Frontiers in Public Health, 2022)
Even though COVID-19 vaccine has been proved effective, vaccine uptake and coverage has been and still is a great concern across different immigrant groups. Vaccine hesitancy remains a barrier to accept the vaccine among immigrants across the globe—including Norway—despite higher rates of hospitalizations and deaths. This study aimed to explore the opinions and suggestions of immigrants on how to lower the COVID-19 vaccine hesitancy among immigrants in Norway. Qualitative interviews were conducted with 88 persons with different immigrant background. Data was analyzed using framework analysis, utilizing “3Cs model of vaccine hesitancy” as a theoretical framework. The analysis yielded five main themes related to factors that may lower the vaccine hesitancy among immigrants in Norway: (1) Effective cultural communication, (2) Vaccine advocacy through community engagement, (3) Motivating factors, (4) Collaborative efforts via government and healthcare, and (5) Incentives for vaccination. This study enhanced our understanding of factors that according to immigrants themselves may lower the vaccine hesitancy. The insights obtained in this study can contribute to a better understanding of the current status of vaccine uptake among immigrants and can further give directions on how to improve vaccine uptake in these groups in Norway.